Advances in spacecraft micro-vibration suppression methods. (1st April 2023) - Jiao, Xiaolei; Zhang, Jinxiu; Li, Wenbo; Wang, Youyi; Ma, Wenlai; Zhao, Yang
Abstract: The micro-vibration generated by various disturbance sources on spacecraft seriously affects the observation and imaging accuracy. Thus, some measures must be taken to isolate such micro-vibration. The most cost-effective choices involve installing vibration isolation devices at either the disturbance sources or the payloads. The selection of a reasonable micro-vibration isolation device benefits the suppression effect of micro-vibration and improves the design of spacecraft. According to the classification of vibration isolation at the disturbance source, transmission path, and payload, we summarized the development status of various types of micro-vibration isolation technologies, and the advantages, disadvantages, and application scope of each vibration isolation technology are discussed. The development direction and problems to be solved in the future are proposed. These are expected to provide a useful reference frame for researchers and engineers working in the field of spacecraft micro-vibration isolation technology.